Development and characterization of fast dissolving tablets of doxazosin mesylate by using novel coprocessed super disintegrating technology - P.Vinay Kumar; Ch. Venkatesh; K. Ashwin Kumar (International Journal of Pharmacy and Analytical Research, 2022)
In the present work, an attempt has been made to develop fast disintegrating tablets of Doxazosin mesylate. Novel method of co processed super disintegrates technology was employed to formulate the tablets. All the formulations were prepared by direct compression method. The blend of all the formulations showed good flow properties such as angle of repose, bulk density, tapped density. The prepared tablets were shown good post compression parameters and they passed all the quality control evaluation parameters as per I.P limits. Among all the formulations F14 formulation showed maximum drug release i.e., 99.3% in 4 min hence it is considered as optimized formulation. The F14 formulation contains CP5 as super disintegrate in the concentration of 30 mg. (CP 5 contains Vivasole and polyplasdone XL in 3:1 ratio).